2007
DOI: 10.1111/j.1365-3040.2007.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

The different fates of mitochondria and chloroplasts during dark‐induced senescence in Arabidopsis leaves

Abstract: Senescence is an active process allowing the reallocation of valuable nutrients from the senescing organ towards storage and/or growing tissues. Using Arabidopsis thaliana leaves from both whole darkened plants (DPs) and individually darkened leaves (IDLs), we investigated the fate of mitochondria and chloroplasts during dark-induced leaf senescence. Combining in vivo visualization of fates of the two organelles by three-dimensional reconstructions of abaxial parts of leaves with functional measurements of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
145
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(168 citation statements)
references
References 55 publications
(91 reference statements)
17
145
1
2
Order By: Relevance
“…Besides the change of AtWRKY22 expression and translation, no other obvious differences in morphology or growth were observed between the wild-type and two mutant plants under normal growth conditions (data not shown). Earlier work demonstrated that both H 2 O 2 (David, 1995) and dark (Keench et al, 2007) could induce plant senescence. At-WRKY22 transcription increased continuously with 3% H 2 O 2 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the change of AtWRKY22 expression and translation, no other obvious differences in morphology or growth were observed between the wild-type and two mutant plants under normal growth conditions (data not shown). Earlier work demonstrated that both H 2 O 2 (David, 1995) and dark (Keench et al, 2007) could induce plant senescence. At-WRKY22 transcription increased continuously with 3% H 2 O 2 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Both of dark (Keench et al, 2007) and H 2 O 2 (David, 1995) treatment can induce plant senescence, thus AtWRKY22 might participate in senescence-induced signal transduction pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with our previous work, where an important diminution of the number of mitochondria was observed in leaves subjected to darkinduced senescence. 3 However, although the MT network was highly altered in leaves having lost 75% to 85% of their chlorophyll content, 1 a distinct motility of mitochondria could still be observed (estimated during 40 seconds as shown in Fig. 1C and D), suggesting a conservation of cytoplasmic streaming until the last stage of leaf senescence.…”
Section: Mitochondrial Mobility Is Conserved Until the Latest Stages mentioning
confidence: 99%
“…Other organelles, such as mitochondria and peroxisomes, remain active much longer and provide energy for the cell as well as take over a number of metabolic tasks during this process (Keech et al, 2007;Chrobok et al, 2016). While yeast and animals possess mitochondrial PPases (Lundin et al, 1991;Curbo et al, 2006), so far no mitochondrial PPase has been identified in plants.…”
mentioning
confidence: 99%
“…Usually a carefully orchestrated dismantling of the chloroplast is one of the first events in the senescence process (Keech et al, 2007). Other organelles, such as mitochondria and peroxisomes, remain active much longer and provide energy for the cell as well as take over a number of metabolic tasks during this process (Keech et al, 2007;Chrobok et al, 2016).…”
mentioning
confidence: 99%